Contribuição para o estudo do efeito magnetocalórico inverso - Hingel, Fernanda de Lima (2009)
When we apply a magnetic field on a ferromagnetic material, it is expected that the magnetic order increases with this field and, therefore, its magnetic entropy decreases. This effect is known as magnetocaloric effect (MCE). However, when we apply a magnetic field on an antiferromagnetic or superconductor material, a de- crease in the order of this material may occur and, therefore, the magnetic entropy increases, which means an opposite effect from the previous one. This effect is called the inverse magnetocaloric effect and has been studied in this thesis in the case of an anisotropic antiferromagnetic system. Also a qualitative study for a superconductor magnetic compound has been done, which experimentally shows the inverse magnetocaloric effect in this system. The analysis of an anisotropic antiferromagnet has been done by using the mean field theory and the Bragg-Williams theory in order to theoretically investigate the inverse MCE. We have studied the properties of an antiferromagnetic system and its phase diagram. We have calculated the relevant physical quantities for the MCE, which show the existence of the inverse magnetocaloric effect and how this study can be useful in the characterization of magnetic materials and their phase transitions.